2017
DOI: 10.1080/23320885.2017.1331135
|View full text |Cite
|
Sign up to set email alerts
|

Trigger finger at wrist caused by degenerative changes of the flexor tendon sheath and carpal tunnel syndrome: a case report

Abstract: Trigger finger at wrist is a rare condition. Symptoms include finger triggering, snapping or catching at the wrist level. Carpal tunnel syndrome and median nerve compression neuropathy are almost always associated. We reported one case which was caused by degenerative changes of the flexor tendon sheath and carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The case discussed in this report is the third in the literature in which a giant cell tumor of the flexor tendon sheath causes trigger wrist, with a unique finding of 2 giant cell tumor rather than 1. 5,9 Once diagnosis is made, prompt surgical excision and release are warranted for relief of symptoms and prevention of further consequences of the carpal tunnel compression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case discussed in this report is the third in the literature in which a giant cell tumor of the flexor tendon sheath causes trigger wrist, with a unique finding of 2 giant cell tumor rather than 1. 5,9 Once diagnosis is made, prompt surgical excision and release are warranted for relief of symptoms and prevention of further consequences of the carpal tunnel compression.…”
Section: Discussionmentioning
confidence: 99%
“…The causes reported in the literature include intrinsic and flexor muscle masses, degenerative changes of the flexor tendon sheath, and avascular necrosis of carpal bones as mentioned. [2][3][4][5][6] The multiplicity of causes and the need for localizing the etiology may often necessitate preoperative imaging of the hand using magnetic resonance imaging; knowing the cause and localizing it limits the amount of dissection needed for excisional treatment. The case discussed in this report is the third in the literature in which a giant cell tumor of the flexor tendon sheath causes trigger wrist, with a unique finding of 2 giant cell tumor rather than 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Suematsu et al categorized the etiology of trigger wrist in three groups; tumor, anomalous muscle, or both, other pathologies have been recently described for trigger wrist [5]. Wang et al reported a case of trigger wrist, in which the degenerative changes of the flexor tendon sheath was the underlying cause [7]. Wakasugi et al reported a case of trigger wrist associated with CTS caused by localized amyloidosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical differentiation of trigger wrist is difficult in these cases [6]. Ultrasound imaging can provide a dynamic picture for the tendon triggering and could be helpful if trigger finger at the wrist is suspected [7]. Once the diagnosis is made, surgical management is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%